Validated HOTS-Based Worksheets Enhance Higher-Order Thinking Skills and Impact Geometry Learning Outcomes - Izzati, Aulia Al Tsani; Faizah, Siti (Universitas Negeri Malang, 2024)
This study aims to develop and evaluate worksheets that promote higher-order thinking skills (HOTS) in teaching perimeter and area to primary school students. The worksheets were highly valid, with a score of 94.63%, and were shown to be well aligned with learning objectives through extensive validity and reliability testing. They contain various question types, including multiple-choice, short-answer and essay questions, which encourage students to think critically and creatively. While many students improved their analytical skills, 39% needed to meet the minimum competency standard (KKM). This underscores the necessity for supplementary strategies to support all learners and enhance learning outcomes.